Echogenic cavum septi pellucidi is associated with mild callosal dysgenesis on postnatal MRI. Issue 3 (28th March 2019) - Stanislavsky, Alexandra; Goergen, Stacy
Abstract: We present a previously unreported association between the sonographic finding of an echogenic cavum septi pellucidi (CSP), concurrent hypointense signal within the CSP on fetal MRI and postnatal MR evidence of dysgenesis of the rostrum and genu of the corpus callosum as well as abnormal shortening of the septal leaflets. An echogenic or non‐fluid filled CSP in the fetus at the midtrimester ultrasound is likely to represent a form of mild callosal dysgenesis. Perinatal assessment of vision and endocrine function and clinical follow‐up of neurodevelopment and growth are probably indicated in such cases.